TEACHER’S STRATEGIES ON ENGLISH E-LEARNING CLASSES DURING COVID-19 PANDEMIC (A CASE STUDY AT SENIOR HIGH SCHOOL) - Meita Lesmiaty Khasyar; Desniar Rizky Lestari (JELLi Journal, 2021)
This research is descriptive qualitative research. The objectives of the research is to know what are the teacher’s strategies on English e-learning classes during the COVID-19 pandemic and to what extent do the strategies help the teachers in English e-learning at senior high school. The writer conducted this research in terms of the teaching strategies of english teachers in Taman Islam Senior High School, Putra Pelita Vocational High School and Pelita Bangsa Sejahtera Vocational High School. The writer used observation, interview and documentation for data collecting technique. The results of the research show that (1) the strategies used by teachers in English e-learning classes regarding listening skills include learning done directly or face to face and using songs. Regarding speaking skills include memorizing vocabulary, making video blogs or vlogs, making self introduction and sending the self introduction by voice note. Regarding reading skills include checking background knowledge, giving reading text to analyze, and choosing varied materials. Regarding writing skills include, giving an example of a text about the material, using a video, explaining material via voice note and allowing students to have personal chat. (2) Several strategies used by teachers are very helpful in teaching English e-learning classes during COVID-19 pandemic. The strategies used also make them easier to achieve learning goals